2017
DOI: 10.1186/s40560-016-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic effects of electrical muscle stimulation in the prophylaxis of deep vein thrombosis for intensive care unit patients: a randomized trial

Abstract: BackgroundDeep vein thrombosis (DVT) is a major complication in critical care. There are various methods of prophylaxis, but none of them fully prevent DVT, and each method has adverse effects. Electrical muscle stimulation (EMS) could be a new effective approach to prevent DVT in intensive care unit (ICU) patients. We hypothesized that EMS increases the venous flow of the lower limbs and has a prophylactic effect against the formation of DVT.MethodsThis study included 26 patients admitted to a single ICU. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…We demonstrated that NMES can reduce the incidence of NED. The beneficial effects of NMES to treat NED may have been elicited through improvement in the neuromuscular and systemic circulation [39, 40]. The improvement in blood supply may protect neurons and myofibers against tissue dysoxia, which has been considered an important mechanism to induce axonal degeneration [39, 41].…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that NMES can reduce the incidence of NED. The beneficial effects of NMES to treat NED may have been elicited through improvement in the neuromuscular and systemic circulation [39, 40]. The improvement in blood supply may protect neurons and myofibers against tissue dysoxia, which has been considered an important mechanism to induce axonal degeneration [39, 41].…”
Section: Discussionmentioning
confidence: 99%
“…2 NMES has been shown beneficial for knee ligament surgery, 3 prevention and management of venous diseases, 4 muscle weakness with advanced progressive disease (e.g. chronic respiratory disease, chronic heart failure, thoracic cancer), 5 critically ill patients confined to bed, 6,7 and neurorehabilitation after spinal cord injury (SCI) or stroke. 8 Functional electrical stimulation (FES) is the use of NMES to execute a functional movement (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There was no significant difference in the venous diameter between the baseline and resistance exercise conditions in this study, but the venous flow velocity significantly increased. In a previous study, Ojima et al [ 15 ] reported no differences in the popliteal vein or common femoral vein diameters between the at-rest condition and during electrical muscle stimulation, although peak venous flow velocities were higher during electrical muscle stimulation than at rest. Likewise, the increased venous flow volume resulted primarily from increases in the time-averaged mean flow velocity in this study using rhythmic handgrip exercise.…”
Section: Main Textmentioning
confidence: 95%